1965
DOI: 10.1525/aa.1965.67.3.02a00040
|View full text |Cite
|
Sign up to set email alerts
|

The Patrilocal Band: A Linguistically and Culturally Hybrid Social Unit1

Abstract: N ENDURING and usually unquestioned assumption underlying gen-A eral anthropological theory is that which suggests the "homogeneity" of very simple societies. For the purposes of the development of evolutionary theory, or for the generation of a descriptive ethnography, or for the discussion . of the validity of the "genetic" approach in historical linguistics, it is customarily assumed that "primitive,)' or "simple" or "folk" societies contain individuals who think, and act, and speak more or less alike.* Suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Furthermore, the large number of assemblages in the middle probably reflects the time-averaged reuse of locations on the landscape as well as the general flexibility in settlement and technological strategies. While originally modeled as a relatively clear-cut bipolar opposition, and as long-indicated ethnographically (e.g., Owen, 1965), forager behavior is clearly more complicated and multidimensional, and likely includes elements of both technological strategies. Other complicating factors for unpacking settlement and technological organization might include duration of occupation, frequency of reoccupation, site function, seasonality, and resource procurement activities.…”
Section: All Assemblagesmentioning
confidence: 99%
“…Furthermore, the large number of assemblages in the middle probably reflects the time-averaged reuse of locations on the landscape as well as the general flexibility in settlement and technological strategies. While originally modeled as a relatively clear-cut bipolar opposition, and as long-indicated ethnographically (e.g., Owen, 1965), forager behavior is clearly more complicated and multidimensional, and likely includes elements of both technological strategies. Other complicating factors for unpacking settlement and technological organization might include duration of occupation, frequency of reoccupation, site function, seasonality, and resource procurement activities.…”
Section: All Assemblagesmentioning
confidence: 99%
“…Smith and Johnson's (1986) study of the Nganhcara peoples of Cape York found that women in cross-dialect marriages maintained their patrilects after marriage, while in many Amazon communities linguistic exogamy is strictly practiced (Aikhenvald, 2002(Aikhenvald, , 2003Jackson, 1983). Australian Aboriginals, for example, are a linguistic community where women have been noted to bring non-local linguistic features into their husband's clan (Owen, 1965). In these societies, Owen suggests the result is a hybrid language where 'it is not possible to define one language as the language of the group' (p. 683).…”
Section: Rekinning: Preserving Boundaries Of Relatednessmentioning
confidence: 99%